Accounting and gender: The profile of accounting publications - Lucas, Angela Christina; Silva, Cíntia do Nascimento; Anzilago, Marcielle (Contextus - Revista Contemporânea de Economia e Gestão, 2024)
Background: Considering the representativeness of women in accounting, the social and professional challenges they face due to gender inequalities and given the social role of academia in qualifying this debate, it is necessary to reflect on the spaces that the topic has gained in scientific publications. Purpose: Investigate the profile of publications in Brazilian accounting journals on gender in accounting. Method: Bibliometric survey of 25 Brazilian scientific journals in the area, between January 2010 and December 2020, resulting in 20 articles, tabulated and analyzed using descriptive techniques. Results: These articles were developed mainly by women, with dispersed authorship and works mostly prepared in partnerships of 3 or 4 people. Authors with more than one article do not present the agenda as a core line of their research. 80% of Brazilian accounting journals have already published at least one paper on the subject indicating a general openness, albeit timid in numbers. These publications occurred primarily in scientific journals well rated by CAPES, suggesting that high-impact journals have been paying attention to the topic’s relevance, following an international trend. Conclusions: Gender research in accounting is recent and growing. The studies conducted so far represent an important introduction to the issue, as they denounce and challenge gender inequalities associated with competence, commitment, practice and even what it means to be an accountant, breaking with the reproduction of these notions and power imbalance. Universities and research centers can contribute to this process by encouraging and embracing (or not rejecting) students and researchers interested in the topic, offering financial and technical support to enable research. Academic congresses and scientific journals, in turn, can contribute by opening specialized thematic lines on the subject, as well as launching calls for special issues.